Effects of a prebiotic, Inulin, and a direct fed microbial on growth performance of weanling pigs - Frantz, N.Z.; Nelssen, Jim L.; DeRouchey, Joel M.; Goodband, Robert D.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A 32-day growth study with a total of 252 weanling pigs (18 ± 3 d of age) was conducted to evaluate the effects of a prebiotic, Inulin (a fructooligosaccharide derivative of chicory), and a direct fed microbial (Lactobacillus strain) in diets for weanling pigs. Pigs were fed one of six experimental diets containing: 1) no antibiotic or prebiotic (negative control); 2) carbadox (50 g/ton, positive control); 3) direct fed microbial (DFM, 0.1%); 4) Inulin (0.5% and 0.2% of phase I and phase II diets, respectively); 5) carbadox plus DFM; or 6) carbadox plus Inulin. Pigs fed carbadox improved (P<0.04) ADG from d 0 to 14, 14 to 32, and overall (0 to 32) compared to pigs fed diets without carbadox. Pigs fed diets containing carbadox increased (P<0.01) ADFI from d 0 to 14 and tended to have increased (P<0.06) ADFI overall compared to pigs fed diets without carbadox. No differences in ADG or ADFI were seen for pigs fed diets containing either Inulin or the DFM compared to pigs fed diets without Inulin or DFM. Pigs fed the DFM had poorer feed efficiency d 0 to 14 (P<0.03), 14 to 32 (P<0.01), and overall (P<0.01) compared to those fed diets without DFM. Also, there was a trend for pigs fed diets containing Inulin to have poorer feed efficiency (P<0.07) from d 14 to 32 and overall when compared to pigs fed diets without Inulin. There were no additive responses for ADG or ADFI when Inulin or DFM were combined with carbadox. Pigs fed diets containing both the DFM and carbadox resulted in poorer feed efficiency (P<0.02) from d 14 to 32 and overall (0 to 32) than pigs fed diets without carbadox or DFM. Pigs fed the diet containing Inulin and carbadox had poorer feed efficiency from d 0 to 14 (P<0.04) compared to pigs fed diets without carbadox or Inulin. In summary, nursery diets containing either Inulin or the DFM did not enhance growth performance; however, carbadox improved ADG and ADFI.
Keywords: Antibiotics; Antimicrobials; Weanling pigs; Swine